2019
DOI: 10.3390/ijms20020375
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Prognostic Role of Carbonic Anhydrase 9 (CAIX) of the Cellular mRNA/Protein Level or Soluble CAIX Protein in Patients with Oral Squamous Cell Carcinoma

Abstract: Carbonic anhydrase 9 (CAIX) is an important protein that stabilizes the extracellular pH value and is transcriptionally regulated by hypoxia-inducible factor 1 (HIF1), but more stable than HIF1α. Here we show a comparative study that examines the prognostic value of CA9 mRNA, CAIX protein of tumor cells and secreted CAIX protein for oral squamous cell carcinoma (OSCC) patients. Tumor samples from 72 OSCC patients and 24 samples of normal tissue were analyzed for CA9 mRNA levels. A total of 158 OSCC samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…It is generally accepted that HIF-1α is a central transcription factor in various cancer types including OSCC [ 44 ]. For many years, our research team focused on the analysis of both hypoxic, but also normoxic stabilization of HIF-1α in this disease [ 26 , 45 , 46 ]. HIF-1α is upregulated in OSCC when oxygen consumption outstrips its supply [ 8 , 9 , 47 ].…”
Section: Hif-1α Stabilization Under Normoxia Its Role In Glutaminmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that HIF-1α is a central transcription factor in various cancer types including OSCC [ 44 ]. For many years, our research team focused on the analysis of both hypoxic, but also normoxic stabilization of HIF-1α in this disease [ 26 , 45 , 46 ]. HIF-1α is upregulated in OSCC when oxygen consumption outstrips its supply [ 8 , 9 , 47 ].…”
Section: Hif-1α Stabilization Under Normoxia Its Role In Glutaminmentioning
confidence: 99%
“…A major target protein upregulated by HIF-1α stabilization is the carbonic anhydrase (CA) IX catalyzing the reaction between protons and CO 2 to H 2 CO 3 . In the metabolic adaptation by the HIF-mediated pathway, CA IX as a central target protein of the HIF system plays an important role [ 45 ]. An elevated expression of CA IX was associated with a poor prognosis of OSCC patients [ 59 ] and with a 5.13-fold increased risk of tumor-related death ( p = 0.017) [ 60 ].…”
Section: Hif-1α Stabilization Under Normoxia Its Role In Glutaminmentioning
confidence: 99%
“…Study found that pancreatic ductal adenocarcinomas (PDACs) cells that express activated KRAS increase expression of CA9, via stabilization of hypoxia-inducible factor 1 subunit alpha (HIF1A) and HIF2A, to regulate pH and glycolysis 25 . Similarly, CA9 is an independent prognostic factor for OSCC patients and therefore a potential therapeutic target 26 . Carbonic anhydrase 6 (CA6, also known as CA-VI; GUSTIN) encodes several isoenzymes of carbonic anhydrase, which are only found in salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that in a recently conducted study, sCAIX levels did not correlate with CAIX mRNA, or protein expression in human oral squamous cell carcinoma tumors [60]. In a study conducted in patients with non-small cell lung cancer, the authors also could not show any association between tumor bound CAIX and sCAIX [61].…”
Section: Plaque Hypoxia: Predictor Of Cardiovascular Disease?mentioning
confidence: 76%
“…However, intra-plaque mechanistic insights were not provided in these studies, nor did the authors provide any clues on whether the oxygen really arrived inside the plaque. In addition, patients suffering from obstructive sleep apnea syndrome (OSAS), which have extensive periods of hypoxemia during their sleep, were shown to have significantly higher circulating levels of triglycerides and total cholesterol compared to body-mass index matched controls [60]. Moreover, blood oxygen restoration with continuous positive airway pressure (cPAP) therapy slightly lowered circulating cholesterol levels in OSA subjects [61].…”
Section: Hypoxia In Cvd and Atherosclerosismentioning
confidence: 99%